Relationship between Sexual pleasure and Marital Satisfaction - Rahmani A. PhD Student; Merghati Khoei E. PhD; Sadeghi N. MSc; Allahgholi L. PhD Student (Iran University of Medical Sciences, 2011)
Background & Aim: Marital satisfaction depends on many factors and one of the most important factors is safe and pleasing sexual relationship. However, there is not sufficient information about these issues in Iran. Therefore the aim of this study was to determine the relationship between sexual and marital satisfaction.   Material & Methods: It was a descriptive - correlational study. The sample includes 292 married males and females who had come to selected hospitals in west of Tehran to visit their reletives. The participants were recruited by convenient sampling. Data was collected by sexual satisfaction and marital satisfaction questionnaires and analyzed using SPSS-PC (ver. 14).   Results: Marital satisfaction was significantly related to sexual satisfaction (p=0/00). Moreover, there was a significant relationship between sexual satisfaction and age difference (p=0/04), duration of marriage (p=0/05), and drug abuse of the participants (p=0/007). Among all variables which have been tested in this study, only age difference was shown to have a significant relationship with marital satisfaction (0/00).   Conclusion: Regarding the relationship between sexual satisfaction and satisfaction with marital life, approaches to teaching young males and females and giving sexual consultation would help them enjoy a successful and satisfactionary marital life.